Safety and pharmacokinetics of a glycoPEGylated recombinant activated factor VII derivative: a randomized first human dose trial in healthy subjects - MØSS, J.; ROSHOLM, A.; LAURÉN, A. (Journal of thrombosis and haemostasis, 2011)
Background: Extensive research is currently ongoing to prolong the half‐life of coagulation factors. One of these techniques is glycoPEGylation, which has also been applied to recombinant activated factor VII (rFVIIa), resulting in a rFVIIa derivative (N7‐GP) with a prolonged terminal half‐life (t1/2). The main clinical purpose of N7‐GP is to provide safe and effective prophylaxis to patients with hemophilia and inhibitors. The prolonged t1/2 of N7‐GP can potentially reduce the dosing frequency and thereby facilitate convenience and compliance, which are two significant barriers to effective prophylaxis. Objectives: To determine the safety and pharmacokinetics of single doses of N7‐GP in healthy men. Methods: A randomized, placebo‐controlled, dose‐escalation trial with five cohorts (N7‐GP dose of 12.5–100 μg kg−1) was performed. In each cohort, eight subjects were randomized to receive N7‐GP (n = 6) or placebo (n = 2). Results: The mean FVIIa activity was measurable for up to at least 72 h after dosing, and the overall mean t1/2 for FVIIa activity was 15 h. The pharmacokinetics of N7‐GP appeared to be dose‐proportional in the dose range investigated. No serious adverse events (including thromboembolic events) were reported. The frequency of adverse events was similar in both the placebo and N7‐GP groups. No neutralizing antibodies against N7‐GP were detected. A pharmacologic effect was apparent from a dose‐dependent statistically significant decrease in the mean prothrombin time in all N7‐GP groups as compared with placebo. Conclusions: N7‐GP had a plasma half‐life of 15 h and a profile that makes it a potential candidate for prophylaxis in patients with hemophilia and inhibitors.